If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + 6)(4y + -5) = 0 Reorder the terms: (6 + 5x)(4y + -5) = 0 Reorder the terms: (6 + 5x)(-5 + 4y) = 0 Multiply (6 + 5x) * (-5 + 4y) (6(-5 + 4y) + 5x * (-5 + 4y)) = 0 ((-5 * 6 + 4y * 6) + 5x * (-5 + 4y)) = 0 ((-30 + 24y) + 5x * (-5 + 4y)) = 0 (-30 + 24y + (-5 * 5x + 4y * 5x)) = 0 (-30 + 24y + (-25x + 20xy)) = 0 Reorder the terms: (-30 + -25x + 20xy + 24y) = 0 (-30 + -25x + 20xy + 24y) = 0 Solving -30 + -25x + 20xy + 24y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '30' to each side of the equation. -30 + -25x + 20xy + 30 + 24y = 0 + 30 Reorder the terms: -30 + 30 + -25x + 20xy + 24y = 0 + 30 Combine like terms: -30 + 30 = 0 0 + -25x + 20xy + 24y = 0 + 30 -25x + 20xy + 24y = 0 + 30 Combine like terms: 0 + 30 = 30 -25x + 20xy + 24y = 30 Add '-24y' to each side of the equation. -25x + 20xy + 24y + -24y = 30 + -24y Combine like terms: 24y + -24y = 0 -25x + 20xy + 0 = 30 + -24y -25x + 20xy = 30 + -24y Reorder the terms: -30 + -25x + 20xy + 24y = 30 + -24y + -30 + 24y Reorder the terms: -30 + -25x + 20xy + 24y = 30 + -30 + -24y + 24y Combine like terms: 30 + -30 = 0 -30 + -25x + 20xy + 24y = 0 + -24y + 24y -30 + -25x + 20xy + 24y = -24y + 24y Combine like terms: -24y + 24y = 0 -30 + -25x + 20xy + 24y = 0 The solution to this equation could not be determined.
| 5(6x-4)=220 | | -5x+1=12x+1 | | R-4=-9+r | | -5x+1=112x+1 | | -2(v-7)=22-6v | | 5a=x | | 2x+3(2-7)=9 | | y(y-1)=-6 | | -4n-5(n-4)=92 | | 1xf=7 | | 2(5)-(14-5)=x | | 2N-9N=6N+52 | | 168=4(-5p+7) | | 2(5)-(14-5)=1 | | 2p+3p=10 | | [x-(3+3i)][x-(3-3i)]= | | -15-3k=-1+4k | | 3x^2+2x-49=0 | | 4x-2=22-8r | | 6=-2n+8n | | -12=-(5x-8)+8(2x-8) | | 10=1+3v-6v | | 2b+12=3b-31 | | 24=6x-2x | | Z+1.5=-2.5 | | 21=-4a+7a | | 5(s+2)=7(s-1) | | 30-3n=2(6-3n) | | 65=2y-5 | | x^2+14x-176=0 | | .9(y+1.4)=-1.8 | | -8t=n+v |